Antiphospholipid antibodies and Mycoplasma pneumoniae infection. Issue 775 (May 1990) - Snowden, N.; Wilson, P. B.; Longson, M.; Pumphrey, R. S.
Abstract : Anticardiolipin antibody levels were measured in 57 patients with Mycoplasma pneumoniae infection and 21 patients with other infections. Significantly more patients in the mycoplasma group had increased IgM and IgG anticardiolipin. Within the mycoplasma group significantly higher titres were found in patients with severe infection (assessed by need for hospital admission) and in patients with cold agglutinins. A tendency for particularly high titres to occur in patients with extra-pulmonary complications was identified.